Cryogenic turbulence test facilities at CEA/SBT. Issue 1 (November 2015) - Rousset, B; Baudet, C; Bon Mardion, M; Bourgoin, M; Braslau, A; Daviaud, F; Diribarne, P; Dubrulle, B; Gagne, Y; Gallet, B; Gibert, M; Girard, A; et al.
Abstract: Recently, CEA Grenoble SBT has designed, built and tested three liquid helium facilities dedicated to turbulence studies. All these experiments can operate either in HeI or HeII within the same campaign. The three facilities utilize moving parts inside liquid helium. The SHREK experiment is a von Kármán swirling flow between 0.72 m diameter counterrotating disks equipped with blades. The HeJet facility is used to produce a liquid helium free jet inside a 0.200 m I.D., 0.47 m length stainless steel cylindrical testing chamber. The OGRES experiment consists of an optical cryostat equipped with a particle injection device and an oscillating grid. We detail specific techniques employed to accommodate these stringent specifications. Solutions for operating these facilities without bubbles nor boiling/cavitation are described. Control parameters as well as Reynolds number and temperature ranges are given.